CORRUPTION AND ITS IMPACT ON NATIONAL DISASTER PERSPECTIVE AL-QASHASH: 59 - Shodiq Ahmad, Mohammad (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2021)
Disasters and calamities in Islam are related to the corrupt actions of human beings. In other words, the cause of a disaster or calamity could be an injustice. This paper aims to explain the Islamic viewpoint on the causes of the catastrophe that occurred in society. This paper also aims to analyze the relationship of bad behavior or injustice prevalent in society to disasters from the perspective of the Noble Qur’an, which is from Surat Al-Qashas, verse 59. The method used in this research is the descriptive method and the analytical method. The first approach is used to explain the meaning contained in Surat Al-Qasas: 59. The analytical approach is used to explain the causes of calamities and disasters that can occur because of people's injustice. This study produces several conclusions. Firstly, there are three important elements in Surat Al-Qasas: 59 which is the criterion for the occurrence of calamities; The word destructive, villages, wrongdoers. Secondly, part of acts of injustice in society; The corrupt leadership and the corrupt society. Third; The way to save humanity from disaster is through choice and actions, the right way of thinking, self-accountability, and integrity in avoiding injustice and corruption.